Optimizing Aqidah and Akhlak Education: Development of E-Module for 7th Grade Students in Islamic Junior High School - Irma, Irma; Nirma, Nirma; Kaharuddin, Kaharuddin; Hamdany, Muhammad Zuljalal Al (South Sulawesi Education Development (SSED), 2024)
This research explains the development of the aqidah akhlak learning e-module for Mts Satu Atap Datok Sulaeman Palopo grade VII students. This study analyzes the needs, validity, and practicality of the aqidah akhlak learning e-module for grade VII MTs one-stop students of Datok Sulaiman Palopo. This type of research is R&D (research and development) with the ADDIE model (Analysis, design, development, implementation, evaluation). The results showed that the aqidah akhlak learning e-module, in terms of validity, had met the very valid criteria with a score of 100% by media experts and 82.14% by material experts. Meeting the criteria is very practical, with a score of 97.75% by educators and 84.89% by students. Thus, the e-module of learning aqidah akhlak, commendable moral material in life, deserves to be used in the learning process.